2018
DOI: 10.2337/db18-0254
|View full text |Cite
|
Sign up to set email alerts
|

Reduced GLP-1 Secretion at 30 Minutes After a 75-g Oral Glucose Load Is Observed in Gestational Diabetes Mellitus: A Prospective Cohort Study

Abstract: Glucagon-like peptide 1 (GLP-1) levels may be reduced in type 2 diabetes, but whether a similar impairment exists in gestational diabetes mellitus (GDM) has not been established. We studied this in a prospective cohort study of pregnant women ( = 144) during oral glucose tolerance test (OGTT). GLP-1, glucose, and insulin were sampled at 30-min intervals during a 2-h 75-g OGTT, and indices of insulin secretion and sensitivity were calculated. In a nested case-control study, women with GDM ( = 19) had 12% lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…This increase in GLP-1 secretion is a product of gastrointestinal tissue expansion, rather than satiety [149]. GLP-1 circulating levels are reduced in pregnant mothers with gestational diabetes [150,151]. However, we have no data about changes in GLP-1 levels during normal pregnancy.…”
Section: Undernutrition and Hormones In Lung Developmentmentioning
confidence: 92%
“…This increase in GLP-1 secretion is a product of gastrointestinal tissue expansion, rather than satiety [149]. GLP-1 circulating levels are reduced in pregnant mothers with gestational diabetes [150,151]. However, we have no data about changes in GLP-1 levels during normal pregnancy.…”
Section: Undernutrition and Hormones In Lung Developmentmentioning
confidence: 92%
“…Copyright © 2022 Society for Endocrinology GDM had decreased levels of GLP-1 throughout gestation (Lencioni et al 2011;Sukumar et al 2018;Mosavat et al 2020). Meanwhile, others have suggested that GLP-1 plays little role in GDM pathogenesis (Hornnes et al 1981;Cypryk et al 2007).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Interpretation GLP-1 and GIP have previously been investigated in women with and without GDM in smaller studies with different results 4,6,7,12 . One study used a different stimulus (mixed meal test) 6 and large BMI differences 6,12 between NGT and GDM subjects might further confound analyses, because BMI negatively associates with GLP-1 and GIP 13 . Similar BMI between groups allowed analyzing impact of GDM on incretin responses, without adiposity as confounder.…”
Section: Main Findingsmentioning
confidence: 99%